Stock market returns and consumption - Marco Di Maggio; Amir Kermani; Kaveh Majlesi (Research Institute of Industrial Economics (IFN), 2018)
This paper employs Swedish data containing security level information on households' stock holdings to investigate how consumption responds to changes in stock market returns. We exploit households' portfolio weights in previous years as an instrument for actual capital gains and dividends payments. We find that unrealized capital gains lead to a marginal propensity to consume (MPC) of 13 percent for the bottom 50% of the wealth distribution but a flat 5 percent for the rest of the distribution. We also find that households' consumption is significantly more responsive to dividend payouts across all parts of the wealth distribution. Our findings are broadly consistent with near-rational behavior in which households optimize their consumption with respect to capital gains and dividends income as if they were separate sources of income.
Keywords: D15; E21; G12; 330; Capital gain; Dividend income; Consumption; Near-rational behavior